The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/myc.12454
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Candida fabianii among clinical isolates biochemically identified as Candida pelliculosa and Candida utilis

Abstract: Clinical yeast isolates belonging to Candida pelliculosa, Candida utilis and Candida fabianii are difficult to distinguish in a routine mycology laboratory using common biochemical tests. The aims of this study were to determine the prevalence of C. pelliculosa, C. utilis and C. fabianii in clinical samples and to compare their minimum inhibitory concentrations (MICs) to systemic antifungals. Two hundred and forty-eight clinical yeast isolates obtained from eight large hospitals in the Czech Republic were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In a recent survey of Czech hospitals, Cy. fabianii has emerged as a significant yeast with the same frequency as Candida lusitaniae and Candida guilliermondii [1]. In addition, Hof et al [16] reported that neonates are relatively prone to the infection by Cy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent survey of Czech hospitals, Cy. fabianii has emerged as a significant yeast with the same frequency as Candida lusitaniae and Candida guilliermondii [1]. In addition, Hof et al [16] reported that neonates are relatively prone to the infection by Cy.…”
Section: Discussionmentioning
confidence: 99%
“…Bhally et al [17] also reported that API 20 C did not identify the yeast. In addition, Svobodova et al [1] mentioned that morphological identification and common biochemical kits cannot distinguish non-albicans clinical isolates such as C. pelliculosa, Cy. jadinii (previously C. utilis), and Cy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Svobodova et al. () compared biochemical identification of clinical yeast isolates to Wickerhamomyces anomalus / Candida pelliculosa and L. jadinii / C. utilis , with MALDI‐TOF MS identification of the same isolates. The MALDI‐TOF, identified the majority of the isolates as Candida fabianii , a non‐QPS species.…”
Section: Assessmentmentioning
confidence: 99%